2005
DOI: 10.1128/aem.71.5.2592-2599.2005
|View full text |Cite
|
Sign up to set email alerts
|

13 C Incorporation into Signature Fatty Acids as an Assay for Carbon Allocation in Arbuscular Mycorrhiza

Abstract: The ubiquitous arbuscular mycorrhizal fungi consume significant amounts of plant assimilated C, but this C flow has been difficult to quantify. The neutral lipid fatty acid 16:15 is a quantitative signature for most arbuscular mycorrhizal fungi in roots and soil. We measured carbon transfer from four plant species to the arbuscular mycorrhizal fungus Glomus intraradices by estimating 13 C enrichment of 16:15 and compared it with 13 C enrichment of total root and mycelial C. Carbon allocation to mycelia was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 53 publications
0
46
0
1
Order By: Relevance
“…Freezedried mycelium (approximately 20 g) or ball-milled root material (approximately 100 g) was enclosed in tin capsules, and the 13 C atom% was determined with an isotope ratio mass spectrometer (20-20 stable isotope analyzer) interfaced with an ANCA-NT combustion module (PDZ Europa Scientific Instruments, Crewe, United Kingdom). Fatty acid methyl esters (prepared as described above) were analyzed with an isotope ratio mass spectrometer interfaced with a Hewlett-Packard gas chromatograph in order to determine the 13 C atom% in neutral lipid fatty acids (NLFA) and phospholipid fatty acids (25). The gas chromatograph was equipped with a 50-m HP5 capillary column (Hewlett-Packard), and He was used as the carrier gas.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Freezedried mycelium (approximately 20 g) or ball-milled root material (approximately 100 g) was enclosed in tin capsules, and the 13 C atom% was determined with an isotope ratio mass spectrometer (20-20 stable isotope analyzer) interfaced with an ANCA-NT combustion module (PDZ Europa Scientific Instruments, Crewe, United Kingdom). Fatty acid methyl esters (prepared as described above) were analyzed with an isotope ratio mass spectrometer interfaced with a Hewlett-Packard gas chromatograph in order to determine the 13 C atom% in neutral lipid fatty acids (NLFA) and phospholipid fatty acids (25). The gas chromatograph was equipped with a 50-m HP5 capillary column (Hewlett-Packard), and He was used as the carrier gas.…”
Section: Methodsmentioning
confidence: 99%
“…Lipids were extracted from mycelia and mycorrhizal roots by vortexing (1 min) in 10 ml of a one-phase mixture containing citrate buffer, methanol, and chloroform (0.8:2:1, vol/vol/vol; pH 4.0). The lipids were fractionated into neutral lipids, glycolipids, and phospholipids on prepacked silica columns (100-mg sorbent mass; Varian Medical Systems, Palo Alto, CA) by elution with 1.5 ml chloroform, 6 ml acetone, and 1.5 ml methanol, respectively (25). The fatty acid residues in neutral lipids and phospholipids were transformed into free fatty acid methyl esters and analyzed by gas chromatography by using a 50-m HP5 capillary fused silica column (Hewlett-Packard, Wilmington, DE) with H 2 as the carrier gas (11).…”
Section: Methodsmentioning
confidence: 99%
“…Several monounsaturated FAMEs were observed that are common across taxa, but 18:1u9 is common to both fungi and Gram-positive bacteria (Bååth, 2003;Vestle and White, 1989). Further, enrichment of general fungal biomarkers such as 16:1u5 (Olsson et al, 1995(Olsson et al, , 2003, 18:1u7 (Olsson, 1999) and 18:2u9,12 (Frostegård and Bååth, 1996;Zelles, 1999;Zechmeister-Bolternstern et al, 2011) indicates that fungi (e.g., ectomycorrhizal and arbuscular mycorrhizal etc.) were possibly actively consuming biomass and/or exudates of the S 2 O 3 2À activated consortium (cross-feeding?).…”
Section: Isotopic Labelling Incubationsmentioning
confidence: 99%
“…However, the nutrients stored in spores may reflect not only the need for formation of new fungal biomass but also that of the plants that are being colonized. The establishment of new symbiotic relations could thus depend on the accumulation of plant-limiting nutrients in spores and their transport into the host roots for recognition of a nonparasitic intruder.The nutrient accumulation and distribution in AM fungal spores have not been studied in as much detail as carbon accumulation has (32), although there are clear links between the nutrient availability and C metabolism (16,17,18). Quantitative analysis of elemental composition in AM fungal mycelia is crucial for our understanding of the distribution of nutritional resources.…”
mentioning
confidence: 99%
“…The nutrient accumulation and distribution in AM fungal spores have not been studied in as much detail as carbon accumulation has (32), although there are clear links between the nutrient availability and C metabolism (16,17,18). Quantitative analysis of elemental composition in AM fungal mycelia is crucial for our understanding of the distribution of nutritional resources.…”
mentioning
confidence: 99%